Effect of pilates exercise versus yoga on primary dysmenorrhea in adolescent girls - Engy M. El Nahas; Doaa Tammam Atia; Mai H. Hassan; Ahmed Abd El-Moneim; Sally Mohamed Sae'd Mahmoud (Universidad de Murcia, 2024)
Article accepted. The article will be published here soon. Pending final quality checks.